SULT4A1 haplotype: conflicting results on its role as a biomarker of antipsychotic response. (September 2014) - Wang, Dai; Li, Qingqin; Favis, Reyna; Jadwin, Andrew; Chung, Hedy; Fu, Dong-Jing; Savitz, Adam; Gopal, Srihari; Cohen, Nadine
Aim : Based on previous pharmacogenetic findings, we investigated the possible association between SULT4A1-1 haplotype and antipsychotic treatment response.Materials & methods : Using Mixed Model Repeated Measures, we tested the relationship between SULT4A1-1 status (+ carrier, - noncarrier) and clinical improvement (in Positive and Negative Syndrome Scale total score) among European ancestry patients treated with paliperidone extended release (n = 937), paliperidone palmitate (n = 990), risperidone (n = 507) and olanzapine (n = 381) in 12 schizophrenia, two schizoaffective disorder and three bipolar I disorder trials. SULT4A1-1 haplotype was determined using tagging SNP rs763120.Results : There was no significant difference between SULT4A1-1 (+) and SULT4A1-1 (-) patients for treatment response to paliperidone or olanzapine. SULT4A1-1 (-) patients had better treatment response to risperidone in one schizophrenia trial, but not in another schizophrenia trial or bipolar mania trial.Conclusion : Across three psychiatric disorders (n = 2815 patients), we observed no consistent association between SULT4A1-1 status and atypical antipsychotic effect. Original submitted 11 February 2014; Revision submitted 2 July 2014